2002
DOI: 10.1093/humrep/17.12.3173
|View full text |Cite
|
Sign up to set email alerts
|

Decline in sex ratio at birth after 10-day war in Slovenia: Brief communication

Abstract: Acute psychological stress in relation to a short war in Slovenia resulted 6 to 9 months later in a decrease in the observed sex ratio at birth. Negative changes in sperm motility may be involved in the sex ratio modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 19 publications
3
97
1
2
Order By: Relevance
“…Or it could be the case that women who feel that they do not yet have "enough" sons are both more likely to become pregnant irrespective of high conflict intensity and less likely to report the birth of a girl. Going from mean in utero exposure in the low-intensity district group to the high-intensity group (i.e., an increase of 0.009 monthly average casualties per 1000 inhabitants) leads to an increase in the probability of a female birth by 1.8 ppt, which is comparable to estimates in Zorn et al (2002) (1.4 ppt) and in Ansari-Lari & Saadat (2002) (between 1 and 1.7 ppt).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Or it could be the case that women who feel that they do not yet have "enough" sons are both more likely to become pregnant irrespective of high conflict intensity and less likely to report the birth of a girl. Going from mean in utero exposure in the low-intensity district group to the high-intensity group (i.e., an increase of 0.009 monthly average casualties per 1000 inhabitants) leads to an increase in the probability of a female birth by 1.8 ppt, which is comparable to estimates in Zorn et al (2002) (1.4 ppt) and in Ansari-Lari & Saadat (2002) (between 1 and 1.7 ppt).…”
mentioning
confidence: 74%
“…Studies testing for changes in the sex-ratio following recent wars have found no effect (Polasek et al 2005) or found a decrease in the sex-ratio (Zorn et al (2002); Ansari-Lari & Saadat (2002)) when comparing the (unconditional) odds ratio of being male during the war compared to beforeand after the war.…”
Section: Civil Conflict and Maternal Conditionmentioning
confidence: 99%
“…The reasons for the discrepancy in the sex distribution at birth are uncertain, but a large number of factors have been implicated as influencing this ratio. 1,2 Factors that reduce the M/T ratio (i.e., lead to relatively fewer male births) include toxins, 1,2 privation and famine, 3 natural calamities, 4 short wars, 5 and elements that induce stress in populations. Examples of the latter include political events such as terrorist attacks, as evidenced in New York after the attacks of .…”
Section: Introductionmentioning
confidence: 99%
“…Factors known to influence the genetic sex of the newborn are: maternal age [1], birth order of the child [2] and stress due to natural disasters [3] or war [4]. Other factors, such as ethnicity [5,6], length of follicular phase [1,7,8] and, diabetes [7] are also suspected to change the sex ratio.…”
Section: Introductionmentioning
confidence: 99%